Zambia CAADP bienniel review brief: Africa agriculture scorecard performance and lessons - Sikombe, Derrick; Mbewe, Christopher; Matchaya, Greenwell C.; Nhemachena, Charles; Nhlengethwa, Sibusiso (International Food Policy Research Institute, 2019)
The agriculture sector is central to the development of Zambia’s economy. It is the key element in achieving sustainable economic growth, job creation, poverty reduction, and foreign exchange earnings for the country. This is because Zambia has immense natural resources, including water and fertile soils, to support agricultural activities. In addition to producing primary agricultural commodities, the sector also provides raw materials for industrial development through agro-processing. Increased production of major agricultural commodities in the crops, livestock, and fisheries subsectors can contribute positively to the country’s gross domestic product (GDP). Therefore, the steady and sustained development of agriculture is crucial for the continued development of the Zambian economy.